SPEECH DEVELOPMENT IN PRIMARY SCHOOL STUDENTS THROUGH MUSICAL AND DIDACTIC GAMES - Eshmurodova Durdona Uktamovna (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article examines the pedagogical potential of musical and educational games for speech development in primary school children. Particular attention is paid to the relationship between musical activity and the development of phonemic awareness, rhythmic and intonational expressiveness, and vocabulary in elementary school children. Classifications of musical and educational games are presented: rhythmic, intonational and rhythmic, narrative and musical, as well as games for developing memory and attention. The principles of organizing lessons are described, including game-based motivation, the combination of speech and movement, the gradual increase in difficulty of tasks, and the repetition of exercises. It is emphasized that the regular use of musical and educational methods contributes to the development of not only speech skills but also the cognitive, social, and emotional competencies of students. This article is intended for primary school teachers, speech therapists, and specialists in musical development of children and can serve as a basis for the implementation of innovative speech teaching methods in the educational process.